1998
DOI: 10.1115/1.2824323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Channel Orientation of Local Heat (Mass) Transfer Distributions in a Rotating Two-Pass Square Channel With Smooth Walls

Abstract: Naphthalene sublimation experiments have been conducted to study the effects of channel orientation, rotational Coriolis force, and a sharp turn, on the local heat (mass) transfer distributions in a two-pass square channel with a sharp turn and smooth walls, rotating about a perpendicular axis. The test channel was oriented so that the direction of rotation was perpendicular to or at a 45 deg angle to the leading and trailing walls. The Reynolds number was kept at 5,500 and the rotation number ranged up to 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…8 and 9 are quite similar to those in channels with all smooth walls and with transverse ribs in the first pass only (Park, 1996). With increasing rotation number, the mass transfer along the outer edges of the leading wall in the turn increases significantly.…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…8 and 9 are quite similar to those in channels with all smooth walls and with transverse ribs in the first pass only (Park, 1996). With increasing rotation number, the mass transfer along the outer edges of the leading wall in the turn increases significantly.…”
Section: Presentation and Discussion Of Resultssupporting
confidence: 60%
“…Increasing the rotational speed causes larger velocity and concentration gradients near the trailing wall and smaller gradients near the leading wall, increasing the difference between the mass transfer on the two walls. (Park, 1996).…”
Section: Presentation and Discussion Of Resultsmentioning
confidence: 99%
“…It was found that the sharp turn enhances the heat transfer but with large friction losses. The effect of sharp turning flows in a two-pass square channel with smooth walls using the naphthalene mass transfer technique was reported by Park et al [15]. They found very large spanwise variation in mass (heat) transfer at the turn and upstream of the outlet pass.…”
Section: List Of Symbolsmentioning
confidence: 87%
“…Mass transfer processes abound in the world around. Park and Lau [9] ) and Park et.al. [10] Study the effect of rotational Coriolis force experimentally on mass transfer distribution.…”
Section: Introductionmentioning
confidence: 99%